Mitochondrial transplantation: a promising strategy for treating degenerative joint diseases - Hong Luo; Yue Lai; Weili Tang; Guoyou Wang; Jianlin Shen; Huan Liu (Journal of Translational Medicine, 2024)
Abstract The prevalence of age-related degenerative joint diseases, particularly intervertebral disc degeneration and osteoarthritis, is increasing, thereby posing significant challenges for the elderly population. Mitochondrial dysfunction is a critical factor in the etiology and progression of these disorders. Therapeutic interventions that incorporate mitochondrial transplantation exhibit considerable promise by increasing mitochondrial numbers and improving their functionality. Existing evidence suggests that exogenous mitochondrial therapy improves clinical outcomes for patients with degenerative joint diseases. This review elucidates the mitochondrial abnormalities associated with degenerative joint diseases and examines the mechanisms of mitochondrial intercellular transfer and artificial mitochondrial transplantation. Furthermore, therapeutic strategies for mitochondrial transplantation in degenerative joint diseases are synthesized, and the concept of engineered mitochondrial transplantation is proposed.